Enforcement and Protection of Children's Rights Victims Criminal Actions - Eleanora, Fransiska Novita (Kertha Patrika, 2020)
The purpose of this study is to determine the protection and enforcement of children as victims of criminal acts in obtaining their rights through restitution in the form of compensation charged to the perpetrators of criminal acts. Protection of the existence of children's rights is the responsibility of all parties, including their parents as the family of the child, because from birth the child has obtained his rights, which is primarily his right to live, and be raised. It aims to protect children from all threats, and intimidation, as well as violence from physical and psychological, sexual and neglect of children and not also the existence of discrimination, but provides a sense of comfort and safety wherever the child is, free from all obstacles or disturbances, so everything prioritizes the best interests of the child, and does not result in the child as a victim of a crime, and causes the child to suffer a form of enforcement of the rights of the child who has been violated and punish the offender according to applicable law, so that there is a deterrent effect and does not repeat his actions. Normative juridical research methods used by reviewing literature or books as well as legislation relating to the problem to be examined. The resultsof this study are (1) protection and enforcement of children's rights, namely rehabilitation, compensation and legal assistance in accordance with the provisions of the child protection law Number 35 of 2014 concerning amendment of law number 23 of 2002, especially promoting the existence of children’s rights (2) the constraints faced are lack of public awareness of cases affecting children, legislation is not fully in favor of children, in terms of restitution law enforcement officials have different interpretations.